2022
DOI: 10.1002/ctm2.763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymerised type I collagen on hyperinflammation of adult outpatients with symptomatic COVID‐19

Abstract: Dear Editor, Although dexamethasone is approved for the hyperinflammation treatment of hospitalised COVID-19 patients, nonhospitalised patients do not benefit from this therapy. 1 A potential drug for treating COVID-19 patients is polymerised type I collagen (PTIC). A downregulator of proinflammatory cytokines, adhesion molecules (ELAM-1, VCAM-1, and ICAM-1), cyclooxygenase (Cox)-1 enzyme and the collagenases expression through the modulation of transcription of factor NF-kB. [2][3][4][5][6] The intramuscular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…While bovine collagen is used for many purposes, porcine collagen is almost exclusively used for the treatment of diseases belonging to the musculoskeletal apparatus [ 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ] (NCT02539030, NCT02519881, NCT02539095), followed by the integumental apparatus [ 67 , 76 , 86 , 87 , 147 , 148 , 149 , 150 , 151 , 152 ] (NCT03844529, NCT00891774, NCT00929071) and gastrointestinal apparatus [ 116 , 117 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. Only recently porcine collagen potential has been explored for the treatment of facial nerve palsy [ 160 ] and for the treatment of COVID-19 due hyperinflammation [ 161 , 162 ] (NCT04517162). However, despite their wide use and effectiveness, bovine and porcine collagens suffer from cultural or religious concerns (bovine collagen: Sikh, Buddhism; porcine collagen: Jewish, Islamic faiths), which restricted their applicative potential [ 18 , 19 ].…”
Section: Collagen-based Injectable Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While bovine collagen is used for many purposes, porcine collagen is almost exclusively used for the treatment of diseases belonging to the musculoskeletal apparatus [ 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ] (NCT02539030, NCT02519881, NCT02539095), followed by the integumental apparatus [ 67 , 76 , 86 , 87 , 147 , 148 , 149 , 150 , 151 , 152 ] (NCT03844529, NCT00891774, NCT00929071) and gastrointestinal apparatus [ 116 , 117 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. Only recently porcine collagen potential has been explored for the treatment of facial nerve palsy [ 160 ] and for the treatment of COVID-19 due hyperinflammation [ 161 , 162 ] (NCT04517162). However, despite their wide use and effectiveness, bovine and porcine collagens suffer from cultural or religious concerns (bovine collagen: Sikh, Buddhism; porcine collagen: Jewish, Islamic faiths), which restricted their applicative potential [ 18 , 19 ].…”
Section: Collagen-based Injectable Formulationsmentioning
confidence: 99%
“…New experimentations using collagen-based formulations were performed for non-standard clinical applications such as facial nerve rehabilitation after palsy [ 160 , 211 ], organ protection during thermal ablation [ 129 ], COVID-19 related hyperinflammation [ 161 , 162 ] (NCT04517162), artery aneurysms closure [ 128 , 213 ], blood volume augmentation [ 127 , 214 ] and the treatment of chronic ischemic heart diseases [ 226 ].…”
Section: Clinical Efficacy Of Collagen-based Injectable Implantsmentioning
confidence: 99%
“…A recent randomised, placebo‐controlled clinical trial demonstrated an innovative approach of treating symptomatic outpatient COVID‐19 infection by intramuscular injection of polymerised type I collagen (PTIC). 2 It was shown that PTIC has immunomodulatory properties and reduces the excessive release of inflammatory mediators arising due to cytokine release syndrome, which determines the clinical course, especially in the second week of infection. One day after completing the treatment, the patients in the treatment group presented a significant increase in mean oxygen saturation readings with values of 92% or higher as well as a shorter duration of symptoms (Figure 1 ).…”
Section: Ecm Remodeling and Inflammationmentioning
confidence: 99%
“…One day after completing the treatment, the patients in the treatment group presented a significant increase in mean oxygen saturation readings with values of 92% or higher as well as a shorter duration of symptoms (Figure 1). 2 The present study delivers a novel approach of targeting systemic inflammation by administration of an F I G U R E 1 Polymerised type I collagen (PTIC) exhibits immunomodulatory effects in COVID-19. The PTIC-treated group showed significant improvement in disease severity.…”
Section: Ecm Remodeling and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation